Communication skills as a bridge between medical and public health education: the case of Greek medical students - Karakolias, Stefanos; Tagarakis, Georgios; Polyzos, Nikolaos (Frontiers in Public Health, 2025)
Effective communication skills are a critical yet often neglected bridge between individual-focused medical education and population-oriented public health goals. Using the Greek medical system as a case study, this paper highlights a significant gap in formal training, finding that only three of the seven medical schools offer dedicated communication modules, with just two being core courses and representing less than 1% of the total ECTS credits. The study contends that this lack of prioritization undermines patient-centered care and broader public health education. Effective provider–patient communication is shown to foster trust, improve treatment adherence, and enhance health literacy, which empowers individuals and communities to make informed health decisions. The study concludes by calling for systematic curricular reform, advocating for the integration of communication and health literacy as core, longitudinal components throughout medical education. It recommends employing simulation-based learning, continuous assessment, and faculty development to ensure that future physicians are equipped to simultaneously improve individual patient outcomes while advancing broader population health goals.